2019
DOI: 10.1186/s13046-019-1466-7
|View full text |Cite
|
Sign up to set email alerts
|

PES1 promotes BET inhibitors resistance and cells proliferation through increasing c-Myc expression in pancreatic cancer

Abstract: sBackgroundOverexpressed PES1 promotes carcinogenesis in various types of malignant tumors. However, the biological role and clinical significance of PES1 in pancreatic cancer are still unexplored.MethodsThe expression level of PES1 in pancreatic cancer cell lines and pancreatic cancer patient samples was determined using Western Blotting analysis, RT-qPCR analysis, immunohistochemical (IHC) analysis of tissue microarray, and the GEPIA web tool. MTS assay, colony formation assay, and xenograft tumor assay were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…The discovery of some promising molecular targets for the treatment of PDAC provided a new direction for the diagnosis and treatment of PDAC. For example, Jin et al reported that, PES1 might be a promoting factor of tumor growth and a PDAC prognosis associated protein [23]. Goehrig et al found that, βig-h3 stromal-derived protein is a main factor driving the immune paracrine interaction mechanism of PDAC, which might be novel target in PDAC treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of some promising molecular targets for the treatment of PDAC provided a new direction for the diagnosis and treatment of PDAC. For example, Jin et al reported that, PES1 might be a promoting factor of tumor growth and a PDAC prognosis associated protein [23]. Goehrig et al found that, βig-h3 stromal-derived protein is a main factor driving the immune paracrine interaction mechanism of PDAC, which might be novel target in PDAC treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DEAD-box RNA helicase 56 (DDX56) is involved in the assembly of the 60S large ribosomal subunit and has been associated with lymphatic invasion and distant metastasis in CRC [ 33 ]. Pescadillo ribosomal biogenesis factor 1 (PES1), which has been reported as an independent poor prognostic factor in pancreatic cancer patients [ 34 ], is essential for 60S ribosomal subunit maturation and pre-rRNA processing [ 35 ]. Therefore, we speculated that the regulation of ribosome biogenesis by GTPBP4 plays an essential role in various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that high mRNA expression of c-Myc has been associated with drug resistance in pancreatic cancer and HPV-negative neck squamous cell carcinoma cells (33,34). It has also been shown that downregulation of c-Myc mRNA expression using siRNA could improve the efficacy of DEX in treatment of ALL (35).…”
Section: Sal Overcomes Dex-resistance In the Cem-c1 Cells By Downregulating C-myc Protein And Mrna Expressionmentioning
confidence: 99%